Applied continuous delivery - Long, Josh (Pearson, 2018)
"Software is eating the world. Many of today's most successful businesses are software businesses, able to iterate and deliver new value to their customers faster and faster. Can you keep up? It's tempting to think that these organizations are all startups and that anything is easy at that size, but that would be a mistake that ignores the likes of Google, Amazon, Twitter, Apple, Netflix, and more. These organizations continue to excel at innovation. How? These organizations, and many others, work hard to reduce the cost of change. They are agile. That agility permeates everything they do from culture to code and results in value for their users. in Josh Long and Marcin Grzejszczak in this video, and learn how to continuously deliver software like the pros with the Pivotal stack and culture using tools like Spring Boot, Cloud Foundry, Concourse, Spring Cloud Contracts, and so much more."--Resource description page
Title from title screen (viewed November 9, 2017)
Keywords: Spring (Software framework); Cloud computing; Application software -- Development; Infonuagique; Logiciels d'application; Développement; Application software; Development